Beyond Power Politics: How Ideology Motivates Threat Perception—and International Relations. (October 2022) - Gries, Peter
A growing literature demonstrates that ideology shapes international relations. But just how does ideology have its effect? This article develops an integrated model of mediators and moderators of the impact of ideology on foreign policy. Specifically, it hypothesizes that ideologically motivated perceptions of threat and national power sequentially mediate the impact of individual-level ideologies on foreign policy preferences, and that in/out-group social categorization processes moderate the relationship. We interrogate these propositions with three plausibility probe case studies. The conclusion discusses which aspects of the model were best supported by the plausibility probes—and suggests hypotheses for future causal testing.